2018
DOI: 10.1017/s1366728917000761
|View full text |Cite
|
Sign up to set email alerts
|

Cross-modal priming in bilingual sentence processing

Abstract: This paper provides a concise overview of the cross-modal priming methodology, it presents a selection of key studies to illustrate how this method can be used to address lexical and syntactic processing and discusses advantages and disadvantages, along with issues that need to be taken into consideration when designing studies that address sentence processing in bilinguals.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 21 publications
0
5
0
Order By: Relevance
“…), while poorest performance is found in clitic structures. Earlier research shows that certain structures such as wh-questions and relative clauses are associated with more persistent problems in bilingual language development (see Ibrahim & Hamann, 2017; Lillo-Martin, Koulidobrova, Quadros, & Chen Pichler, 2012; Marinis, 2018; Piñar et al, 2017; Roesch & Chondrogianni, 2016; Stavrakaki, Tasioudi, & Guasti, 2015). Thus, an additional analysis on structure errors alone was carried out in order to (a) disentangle syntax-only errors from all other types and (b) identify the specific structures that are more problematic for bilingual and monolingual children.…”
Section: Discussionmentioning
confidence: 99%
“…), while poorest performance is found in clitic structures. Earlier research shows that certain structures such as wh-questions and relative clauses are associated with more persistent problems in bilingual language development (see Ibrahim & Hamann, 2017; Lillo-Martin, Koulidobrova, Quadros, & Chen Pichler, 2012; Marinis, 2018; Piñar et al, 2017; Roesch & Chondrogianni, 2016; Stavrakaki, Tasioudi, & Guasti, 2015). Thus, an additional analysis on structure errors alone was carried out in order to (a) disentangle syntax-only errors from all other types and (b) identify the specific structures that are more problematic for bilingual and monolingual children.…”
Section: Discussionmentioning
confidence: 99%
“…Offline tasks such as untimed acceptability judgement tasks are typically considered conducive to testing and measuring explicit knowledge, while online tasks such as cross-modal priming tasks (CMPTs), which detect participants' automatic response to stimuli, are considered appropriate for measuring implicit knowledge (cf. Godfroid et al, 2015;Marinis, 2010Marinis, , 2018. The majority of L3 studies in the literature reported data elicited from offline tasks and not much work on L3 morphosyntax has employed online processing methods (see reviews in De Bot & Jaensch, 2015;Rothman et al, 2019).…”
Section: Online Vs Offline Tasks In L3 Researchmentioning
confidence: 99%
“…The CMPT is a well-established method for detecting activation of lexical and syntactic information during sentence comprehension, which integrates verbal and visual modalities (cf. Hu & Jiang, 2011;Marinis, 2018). This method was adapted in our study, in which all tokens were mini dialogues consisting of two sentences (uttered respectively by Speakers A and B), as illustrated in ( 5)-( 8).…”
Section: Materials and Proceduresmentioning
confidence: 99%
“…Note that in such contexts, the putative gap position and the subcategorizer (love) are adjacent. In order to 10 For a critical review of CMLP in the context of bilingualism research, see Heredia & Cieślicka (2019); for an overview of the methodology, see Marinis (2018). distinguish these accounts on the basis of reactivation data, experimental materials would need to be devised in which the gap position and the subcategorizer are not adjacent; see, for example, Nicol (1993) andFeatherston (2001: Experiments 1-3).…”
Section: The Psychological Reality Of Empty Categoriesmentioning
confidence: 99%